CORRELATION OF AGE AND PARITY WITH HYPERTENSION INCIDENCE AMONG PREGNANT WOMEN - Fauziah, Nur Alfi; Praselia, Ovie (Proceedings of the International Conference on Applied Science and Health, 2017)
Aim:To determine the correlation between age and parity with the incidence of hypertension in pregnantÂ women.Methods: This type of research is a quantitative approach with Case Control design. For statistics, this study used chi-square test. The sample of this research is 200 pregnant women with purposive sampling technique. The data used are secondary data. Research instrument using checklists. The technique of collecting data using observation sheet. Results: The statistic test found that the proportion of age <20 years -> 35 years experienced hypertension that is 60.5% (72 pregnant women) and the proportion of primipara parity experienced hypertension that is 63.8% (90 pregnant women). The result of the statistical test of chi-square analysis relation between maternal age and hypertension with p-value = 0.001 and relationship between parity and hypertension with p-value = 0.000. Conclusion:There is a relationship between age and parity of pregnant women with the incidence of hypertension.Â